A FRONTEIRA DE COMMODITIES NA AMAZÔNIA (2000-2019): AS MUDANÇAS DAS RELAÇÕES RURAL-URBANAS NA REGIÃO METROPOLITANA DE SANTARÉM-PARÁ / The frontier of commodities in the Amazon (2000-2019): changes in rural-urban relations in the Metropolitan Region of Santarém-Pará - Pessôa, Elen Cristina da Silva; do Nascimento, Humberto Miranda (Informe GEPEC, 2022)
O artigo trata do avanço da fronteira de commodities na Amazônia brasileira no período 2000-2019. Seu objetivo é compreender como as relações rural-urbanas estão se transformando na Região Metropolitana de Santarém, no estado do Pará. Busca-se responder à seguinte questão: quais os tipos de impactos que estão mudando a dinâmica das relações rurais e urbanas na região de Santarém? Adota-se a hipótese de que o capital agroexportador que atua na região de Santarém modifica continuamente a configuração do território e impacta suas relações rural-urbanas de diferentes formas. Por fim, mostra-se que a reestruturação econômico-espacial de Santarém foi motivada por grandes investimentos em infraestrutura atrelados à expansão da cultura da soja. Abstract: The paper deals with the advance of the commodities frontier in the Brazilian Amazon in the period 2000-2019. Its objective is to understand how urban-rural relations are changing in the Metropolitan Region of Santarém, in the state of Pará. It seeks to answer the following question: what types of impacts are changing the dynamics of rural and urban relations in the region of Santarem? The hypothesis is adopted that the agro-export capital that operates in the region of Santarém continuously modifies the configuration of the territory and impacts its urban-rural relations in different ways. Finally, it is shown that the economic-spatial restructuring of Santarém was motivated by large investments in infrastructure linked to the expansion of the soybean crop.